Bone Morphogenetic Protein Use and Cancer Risk Among Patients Undergoing Lumbar Arthrodesis: A Case-Cohort Study Using the SEER-Medicare Database. (6th July 2016) - Beachler, Daniel C.; Yanik, Elizabeth L.; Martin, Brook I.; Pfeiffer, Ruth M.; Mirza, Sohail K.; Deyo, Richard A.; Engels, Eric A.
Abstract : Background: Recombinant bone morphogenetic proteins (BMPs) are growth factors utilized in lumbar arthrodeses. Limited data from randomized trials suggest that BMP may increase cancer risk. We sought to evaluate cancer risk and mortality following the use of BMP in lumbar arthrodesis. Methods: Within the linked Surveillance, Epidemiology, and End Results (SEER) Program-Medicare cohort, we conducted a case-cohort study of 7, 278 individuals who were ≥65 years of age and had undergone a lumbar arthrodesis from 2004 to 2011. Of these patients, 3, 627 were individuals in a 5% random subcohort of Medicare enrollees in SEER areas including 191 who developed cancer, and there were 3, 651 individuals outside the subcohort who developed cancer. Weighted Cox proportional-hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for cancer on the basis of exposure to BMP. Results: In the SEER-Medicare subcohort, 30.7% of individuals who underwent a lumbar arthrodesis received BMP. BMP was not associated with overall cancer risk in univariate analyses (HR, 0.92 [95% CI, 0.82 to 1.02]) or after adjustment for demographic characteristics, comorbidities, hospital size, history of cancer, and calendar year (adjusted HR, 0.94 [95% CI, 0.84 to 1.05]). Individual cancer types were also not significantly elevated (p > 0.05 for all) in BMP users compared with nonusers. In addition, BMP use was not associated with a new cancer in people who had cancer prior to undergoing lumbar arthrodesis (adjusted HR, 1.04 [95% CI, 0.71 to 1.52]) or with mortality after a cancer diagnosis (adjusted HR, 1.05 [95% CI, 0.93 to 1.19]). Conclusions: In a large population of elderly U.S. adults undergoing lumbar arthrodesis, BMP use was not associated with cancer risk or mortality. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.